Identifikasi Risiko Dari Penerapan Konstruksi Hijau Dalam Pelaksanaan Proyek Konstruksi Dari Perspektif Kontraktor - Damar, Michelle Sastro; alrizal, fahmi firdaus (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2023)
The risk identification process is an important process, because in the application of green construction there is a possibility of risks arising in a project. So that the application of green construction must be identified to be able to know what risks are the basis for implementing green construction and how strategies to overcome and implement green construction in the construction service industry. Analytical Hierarchy Procces or often abbreviated as AHP is a method that can be used to make a decision from a variety of alternatives with a hierarchical structure model. The AHP model will describe problems that have many criteria, sub criteria, and alternatives into a hierarchical chart or structure. AHP can determine the occurrence of risk, the magnitude of risk impact, and the criticality of risk from the Sub-Criteria, Criteria, and Levels of risk obtained. The results show that Macroeconomic Risk, Risk in Aspects of Contractual Issues, and Risk in Aspects of Technical Issues are the top three on the risk criteria. In addition, the overall risk still shows that risk management is still needed for green construction. there are several suggestions in the research, namely the Contractor pays more attention to the risks in the application of green construction in an effort to reduce or minimize the risks that will occur and the risk identification of the application of green construction in the implementation of further construction projects on the results of risk level indicators on the concept of green construction.